2020
DOI: 10.1186/s42408-020-00074-0
|View full text |Cite
|
Sign up to set email alerts
|

Fire and distance from unburned forest influence bird assemblages in Southern Andean Yungas of Northwest Argentina: a case study

Abstract: Background: Wildfires affect vegetation structure, functions, and other attributes of forest ecosystems. Among these attributes, bird assemblages may be influenced by the distance from undisturbed to fire-disturbed forests. Information about this influence is essential for designing management plans aimed at conserving birds' diversity in undisturbed forests, which contributes to their sustainability. In Northwest Argentina, timber extraction and mancaused fires threaten the sustainability of Southern Andean Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The size of each black dot is proportional to its weight or contribution to the overall mean calculation. Asterisk (*) denotes a significant difference (Q-between [Q b ] statistics) among categories (* = P < 0.05) ecosystems (e.g., Barlow and Peres 2004;Fontaine and Kennedy 2012;Mestre et al 2013;Albanesi et al 2014), although there are exceptions (e.g., Fontaine and Kennedy 2012;Lee 2018;Morales et al 2020), such as the group of birds known as cavity excavators (i.e., woodpeckers [Picidae]), that take advantage of both the softness of the wood of recently burned trees (i.e., snags) for making their cavities (Schepps et al 1999;Winkler and Christie 2002;Lorenz et al 2015) and the higher amount of food (insect and other invertebrates) found in that substrate right after the fire (Murphy and Lehnhausen 1998;Nappi et al 2003).…”
Section: Effect Of Fire On the Response Variablesmentioning
confidence: 99%
“…The size of each black dot is proportional to its weight or contribution to the overall mean calculation. Asterisk (*) denotes a significant difference (Q-between [Q b ] statistics) among categories (* = P < 0.05) ecosystems (e.g., Barlow and Peres 2004;Fontaine and Kennedy 2012;Mestre et al 2013;Albanesi et al 2014), although there are exceptions (e.g., Fontaine and Kennedy 2012;Lee 2018;Morales et al 2020), such as the group of birds known as cavity excavators (i.e., woodpeckers [Picidae]), that take advantage of both the softness of the wood of recently burned trees (i.e., snags) for making their cavities (Schepps et al 1999;Winkler and Christie 2002;Lorenz et al 2015) and the higher amount of food (insect and other invertebrates) found in that substrate right after the fire (Murphy and Lehnhausen 1998;Nappi et al 2003).…”
Section: Effect Of Fire On the Response Variablesmentioning
confidence: 99%